MAMACA SEBAGAI MEDIA PENDIDIKAN ISLAM NUSANTARA - Khuluqi, Muhammad Adil; Saihan, Saihan; Masrohatin, Siti (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2025)
The Mamaca tradition in Madura is a form of oral literature rooted in local wisdom and Islamic values, representing the cultural assimilation between Islam and pre-Islamic traditions in Nusantara. Initially practiced as a poetic chant akin to the Javanese Macapat, Mamaca evolved into a didactic medium, narrating stories imbued with religious and moral teachings. This study aims to examine Mamaca as a vehicle for Islamic education in the context of Islam Nusantara, particularly its role in preserving local identity amidst globalization and the influx of transnational ideologies. Using a qualitative approach with descriptive-analytical methods, the research employs fieldwork techniques such as observation, documentation, and structured interviews. The study draws on Mark R. Woodward’s theory of cultural Islam, which views Islam in Java and Madura as a syncretic and mystical tradition rooted in Sufism. The findings reveal that Mamaca functions not merely as a folkloric art form but as a means of internalizing Islamic values through narratives, symbols, and performance, especially in pesantren environments. However, challenges such as generational gaps, declining interest, and cultural shifts threaten the survival of this tradition. The study concludes that revitalizing Mamaca as a character education tool aligned with Islam Nusantara’s principles—tolerance, spirituality, and cultural harmony—can reinforce local Islamic identity. Therefore, Mamaca holds strategic potential as an indigenous educational model that aligns with Nahdlatul Ulama’s vision of moderate and contextual Islam.